Assessing digital leadership of junior high school principals - Ofita, Cherly; Komariah, Aan; Abubakar, Abubakar (Journal of Educational Management and Instruction (JEMIN), 2024)
Digital leaders are not necessarily experts in computer programming; rather, they are individuals capable of leveraging information technology to achieve organizational goals in the current era of digitalization. This research analyzes the digital leadership aspects or dimensions of junior high school principals in Sukabumi City, West Java, Indonesia. Specifically, it examines whether the digital leadership of these principals has met the target, is on target, or still falls short in enhancing the digital competence of 21st-century teachers. The study employs a qualitative descriptive design, utilizing interviews and observations as instruments. Data were collected from three junior high schools, involving three principals and nine teachers in Sukabumi City. The qualitative analysis was conducted using Atlas.Ti version 8. The research findings reveal several obstacles in the implementation of digital initiatives, including budget constraints, insufficient digital competence among teachers, and uneven infrastructure, all of which have hindered effectiveness in meeting the targets. Consequently, the study suggests that principal support, increased teacher literacy, and the formation of innovation teams are crucial for effective digital leadership and the successful achievement of school program targets.